Moon and Earth Radiation Budget Experiment (MERBE) EBAF-like Ed1.1 Solar reflected radiation (2000-03 to 2014-12) - Grant Matthews (PANGAEA, 2021)
The last two US National Academies on Science Decadal survey reports both stressed the vital need to improve the accuracy of orbital climate measurements. They contained comments such as “the single most critical issue for current climate change observations was their lack of accuracy and low confidence in observing the small climate change signals over long decade timescales”. Existing NASA and European measurements are unable to detect such trends that need to be found, because their instruments degrade on-orbit in ways that till now, could not be tracked and compensated for in their released Earth data (i.e. creating spurious trends). This data is from the Moon and Earth Radiation Budget Experiment (MERBE). It uses the constant reflectivity of the Moon as a calibration standard to monitor calibration changes for instruments built for the Clouds and The Earth extquotesingles Radiant Energy System (CERES, on NASA Terra and Aqua platforms). The Earth reflected solar irradiance data here dating from 2000, are perhaps the most stable ERB satellite calibration dataset ever produced. It is free for all to download and compare with climate model simulations run since 2000 up to the present day, to give better confidence in their predictions of future climate change. This is a slight update to a previous version https://doi.pangaea.de/10.1594/PANGAEA.931779 with improved calibration